Kondisi Umat Islam Masa Penjajahan Jepang - Husni, Muhammad (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The study aims to describe the entering process of Japan in Indonesia and to know Islamic society condition and also responds about the colonialization of Japan. This is qualitative research, focuses on literature which concern about Islamic society condition under the colonialization of Japan. The result of this research has found that Japan can made Indonesian people became miserable. Even if was compared to the colonialization of Netherland. However, in this era, Indonesian people have given a chance to manage an organization with fredomly. The impact of this chance, Muslim people felt helped to communicate with clerics by the policy of Japan. The policy was planed by Japan to exploit Muslim people in war. Yet, it wasn’t success and then Moslem people took this situation to proclaim a liberty as Republic of Indonesia